(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This study is devoted to studying the levels of development of students’ communicative competence in the process of learning English. Communicative competence plays an important role in the successful acquisition of a foreign language, since it covers not only grammatical and lexical skills, but also the ability to communicate adequately and effectively. The study examines the assessment methodology and division of students into different levels of communicative competence, and also analyzes the factors influencing its formation. The results obtained will allow us to develop more effective teaching methods aimed at improving students’ communication skills when learning English.